Learn Sprite Kit for iOS game development - Long, Leland (Apress, 2014)
"With Learn Sprite Kit for iOS Game Development, you'll discover how easy it is to create 2D games using the new Sprite Kit framework from Apple. You'll find how simple it is to create a scene, add animated sprites, incorporate edges, play sound effects, and create animated particles for special effects. You'll also use touch events to control your sprites, implement the built-in physics engine, handle sprite collisions and contacts, and much more. To help you in learning how to use all these cool features of Sprite Kit, you'll follow along as we build a complete 2D game for iPhone. By the time you finish the book, you'll have made your own 2D game, and you'll have learned all you need to know to get started on your next masterpiece. What you'll learn: How to add animated sprites to your game scene; Using TouchEvents to have your sprite react to touch input; How to apply realistic physics to your game scene and characters; Handling sprite collisions and contacts with other game elements; Adding game logic for sprite interaction, scoring, levels, and more; Adding a second player and using GameKit. Who this book is for: Beginning developers who have some understanding of object-oriented programming as well as intermediate iOS developers who want to get up to speed quickly with Sprite Kit."--